X²+3x-21=0
1) we solve this square equation:
x=[-3⁺₋√(9+84)] / 2=(-3⁺₋√93)/2
We have two solutions:
x₁=(-3-√93)/2
x₂=(-3+√93)/2
2) we compute the product of the 2 solutions found.
[(-3-√93)/2][(-3+√93)/2] =(-3-√93)(-3+√93) / 4=
=(9-93)/4=-84/4=-21
Answer: the product of the 2 solutions of this equation is -21
To answer the problem above, divide the numerical portion and the exponential portion of the given numbers. 4.5 divided by 9 is 0.5. Furthermore, 10^3 divided by 10^7 is 10^-4. The answer is
0.5 x 10^-4
This may still be written in a standard form,
5 x 10^-5
Thus, the answer is <em>5 x 10^-5</em>.
Answer:
55
Step-by-step explanation:
Well you just plug in 10 as n.. and you get the equation:
![\frac{10(10+1)}{2} \\\frac{10(11)}{2}\\\\\frac{110}{2}\\\\55](https://tex.z-dn.net/?f=%5Cfrac%7B10%2810%2B1%29%7D%7B2%7D%20%5C%5C%5Cfrac%7B10%2811%29%7D%7B2%7D%5C%5C%5C%5C%5Cfrac%7B110%7D%7B2%7D%5C%5C%5C%5C55)
Answer:
2 x 3 + 7 x 2 + 14 x + 12÷ 2x+ 3 = <u> x² +2x+ 4 </u>
Step-by-step explanation:
We multiply the first term 2x of the divisor with a term ( quotient) to get the first term of the dividend. Then we multiply the same term with each term of the divisor and subtract it from the dividend. The process continues unless we get the zero or a much smaller number than the dividend as the remainder
<u> x² +2x+ 4 </u>
2x+3 ║2 x 3 + 7 x 2 + 14 x + 12
2x³ + 3x²
<u> - - </u>
4x² +14x+12
4x²+ 6x
<u> - - </u>
8x+12
8x+12
<u> - - </u>
<u> 0 </u>
Answer:
C
B
A
Step-by-step explanation:
Graph: